2002
DOI: 10.1073/pnas.052596299
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-like recognition of group I introns by a tyrosyl-tRNA synthetase

Abstract: The Neurospora crassa mitochondrial tyrosyl-tRNA synthetase (CYT-18 protein) functions in splicing group I introns by promoting the formation of the catalytically active RNA structure. Previous work suggested that CYT-18 recognizes a conserved tRNA-like structure of the group I intron catalytic core. Here, directed hydroxyl-radical cleavage assays show that the nucleotide-binding fold and C-terminal domains of CYT-18 interact with the expected group I intron cognates of the aminoacyl-acceptor stem and Danticod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…In the cases of two tRNA synthetases, it has been found that their splicing activity is indeed related to their primary functions. The N. crassa mt tyrosyl RS facilitates splicing of a number of mt group I introns by binding to the intron core via its tRNA binding surface (Caprara et al 1996;Myers et al 2002). Likewise, the S. cerevisiae mt leucyl RS, which is involved in the processing of at least two mt yeast introns, promotes splicing via a domain that functions in the editing of misactivated amino acids and binding of the tRNA acceptor helix (Herbert et al 1988;Li et al 1996;Rho et al 2002).…”
Section: Evolutionary Perspectivementioning
confidence: 99%
“…In the cases of two tRNA synthetases, it has been found that their splicing activity is indeed related to their primary functions. The N. crassa mt tyrosyl RS facilitates splicing of a number of mt group I introns by binding to the intron core via its tRNA binding surface (Caprara et al 1996;Myers et al 2002). Likewise, the S. cerevisiae mt leucyl RS, which is involved in the processing of at least two mt yeast introns, promotes splicing via a domain that functions in the editing of misactivated amino acids and binding of the tRNA acceptor helix (Herbert et al 1988;Li et al 1996;Rho et al 2002).…”
Section: Evolutionary Perspectivementioning
confidence: 99%
“…The results of an experiment using buffer conditions favoring Cyt-18 activity (Guo and Lambowitz 1992) are shown. A representative gel including the ⌬ORF mtLSU positive control intron RNA (Myers et al 2002) and two S788 intron RNAs (Acarospora and Lecanora) incubated in the presence (+) or absence (−) of Cyt-18 are presented. For the ⌬ORF mtLSU intron precursor RNAs (Pre), ligated exons RNAs (LE), and excised intron RNAs (Int) are readily seen.…”
Section: Parallel Evolution Of Fungal Rdna Group I and Spliceosomal Imentioning
confidence: 99%
“…The Neurospora crassa mitochondrial (mt) tyrosyl-tRNA synthetase (TyrRS), the CYT-18 protein, functions in splicing group I introns by stabilizing the catalytically active RNA structure (Akins and Lambowitz 1987;Guo and Lambowitz 1992;Mohr et al 1992;Caprara et al 1996a,b;Myers et al 2002). The group I intron catalytic core consists of two extended helical domains, one formed by the coaxial stacking of secondary structure elements P5, P4, and P6 (P4-P6 domain) and the other consisting of P8, P3, P7, and P9 (P3-P9 domain; Michel and Westhof 1990;Cech 1993;Golden et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…CYT-18 interacts with the group I intron catalytic core on the side opposite the active-site cleft (Caprara et al 1996b). Biochemical and genetic studies have led to a model in which CYT-18 binds first to the P4-P6 domain to promote its assembly and then makes additional contacts with the P3-P9 domain to stabilize the two major RNA helical domains in the correct relative orientation to form the intron's active site (Caprara et al 1996a,b;Webb et al 2001;Myers et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation